2023
DOI: 10.1002/aro2.31
|View full text |Cite
|
Sign up to set email alerts
|

Designing and evaluating a cost‐effective single nucleotide polymorphism liquid array for Chinese native chickens

Yifan Liu,
Yanju Shan,
Yunjie Tu
et al.

Abstract: Genotyping plays an important role in breeding and population studies. Currently available genotyping technologies, including solid‐phase chips and sequencing, often have several limitations in their application to local chickens in China, including high costs, insufficient diversity, and poor universality. In the present study, we developed a chicken 5 K single nucleotide polymorphism (SNP) array suitable for breeding and genetic analysis using genotyping by targeted sequencing technology. The chip design was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…This technology combined the advantages of the bead chips and the NGS with features including low cost, high accuracy, and flexible design. GBTS has been widely applied in species such as maize [19], wheat [20], chicken [21,22], pigs [23], sheep [24], and goats [25] but is rarely reported in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…This technology combined the advantages of the bead chips and the NGS with features including low cost, high accuracy, and flexible design. GBTS has been widely applied in species such as maize [19], wheat [20], chicken [21,22], pigs [23], sheep [24], and goats [25] but is rarely reported in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in birds like chickens, there is an average diversity of about one SNP every 200 bases for almost every possible comparison between two lines. Meanwhile, SNPs are common in plants, though their frequency appears to vary from species to species (Liu et al, 2023;Rizk, 2023). For example, in soybeans, one SNP was discovered every 270 bp, whereas in maize, it was found every 60 bp, and in Pisum, the change was noticed by one SNP every 20 bases in intronic regions (Ching et al, 2002;Jing et al, 2007).…”
Section: Introductionmentioning
confidence: 99%